2013
DOI: 10.1074/jbc.m113.461988
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Secondary Promoter within the Human B Cell Receptor Component Gene hCD79b

Abstract: Background: Transcriptional control of hCD79b is critical to B cell function and poorly understood. Results: A fully sufficient and novel secondary promoter was identified within intron 1 of hCD79b. Conclusion: hCD79b has a complex transcriptional structure comprising two competing promoters. Significance: The secondary promoter within hCD79b predicts novel pathways of B cell receptor expression in normal and pathologic settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Thus, to further test HSI-autonomy, we introduced a 1.6-kb interstitial deletion within the −8.0CD79b transgene that removed the hCD79b promoter along with a secondary promoter located within the first intron (− 8.0CD79bΔ1.6 ; Figure 1B ). The removal of these hCD79b promoters eliminates hCD79b transcription in B cells, but not in pituitary ( 25 ). Remarkably, each of 11 genetically distinct − 8.0CD79bΔ1.6 transgenic lines expressed appreciable levels of hCD79b mRNA in the pituitary.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, to further test HSI-autonomy, we introduced a 1.6-kb interstitial deletion within the −8.0CD79b transgene that removed the hCD79b promoter along with a secondary promoter located within the first intron (− 8.0CD79bΔ1.6 ; Figure 1B ). The removal of these hCD79b promoters eliminates hCD79b transcription in B cells, but not in pituitary ( 25 ). Remarkably, each of 11 genetically distinct − 8.0CD79bΔ1.6 transgenic lines expressed appreciable levels of hCD79b mRNA in the pituitary.…”
Section: Resultsmentioning
confidence: 99%
“…The arrows indicate the distance between the HSI core and the center of the most proximal TSS cluster. hGH BAC , 123 kb unmodified human transgenic mouse line (two copies) ( 26 ); CDΔ0.7/hGH BAC , 0.7 kb deletion of 0.5 kb promoter region and exon 1 from hGH BAC (14 copies) ( 25 ); CDΔ1.6/hGH BAC , 1.6 kb deletion of 0.5 kb promoter through exon 2 from the hGH BAC (three copies) ( 23 ); −8.0CD79bΔ1.6 , 1.6 kb deletion of hCD79b promoter through exon 2 from the −8.0CD79b (6 copies); λΔCD/hGH BAC , 3.8 kb λ gene segment replacing hCD79b from hGH BAC (five copies) ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternative promoters may exist in intergenic or intragenic regions [ 30 , 31 ]. Intragenic promoters have been described for transcription of tRNA and other non-coding (nc) RNAs [ 32 , 33 ] as well as protein-coding RNAs [ 31 , 34 38 ]. Recently, it has been reported that intragenic enhancers may act as alternative promoters transcribing multiple exonic poly(A) + RNA (meRNA) from host gene, although the function of meRNA remains unclear [ 39 ].…”
Section: Introductionmentioning
confidence: 99%